Locke and botany. - Anstey, P; Harris, S (2006)
This paper argues that the English philosopher John Locke, who has normally been thought to have had only an amateurish interest in botany, was far more involved in the botanical science of his day than has previously been known. Through the presentation of new evidence deriving from Locke's own herbarium, his manuscript notes, journal and correspondence, it is established that Locke made a modest contribution to early modern botany. It is shown that Locke had close and ongoing relations with the Bobarts, keepers of the Oxford Botanic Garden, and that Locke distributed seeds and plant parts to other botanists, seeds of which the progeny almost certainly ended up in the most important herbaria of the period. Furthermore, it is claimed that the depth of Locke's interest in and practice of botany has a direct bearing on our understanding of his views on the correct method of natural philosophy and on the interpretation of his well known discussion of the nature of species in Book III of his Essay concerning human understanding.